Yield, quality and nutrient uptake of fenugreek (Trigonella foenum-graecum) as influenced by irrigation levels and weed management practices (Indian Journal of Arid Horticulture, 2025)
Fenugreek is an important seed spice crop mainly grown during rabi in Rajasthan, Gujarat, Madhya Pradesh Maharashtra, Haryana, Punjab, Bihar and Andhra Pradesh. The seeds of fenugreek are used as a condiment and sea- soning agent for garnishing and flavourings dishes. In In- dia, water is increasingly becoming scarce and costly due to continuous lowering of water table on account of bur- geoning population.. In India 80 per cent of available wa- ter is used for agriculture. There is a water crisis today but crisis is not about having too little water to satisfy our needs, it is a the crisis of managing water badly resulting in lower water use efficiency. Moreover; water is an indis- pensable for every metabolic activity of plant. Simultaneous emergence and rapid growth of weed leads to severe weed competition with fenugreek for light, moisture, space and nutrients. Weeds are responsible for causing significant losses in crop productivity and quality of product. There- fore, precise information on water and weed management in fenugreek is essential for realising higher yield of fenugreek.
Keywords: geoning population; Simultaneous emergence; essential; fenugreek.